Visfatin/Nampt: An Adipokine with Cardiovascular Impact. (20th October 2013) - Romacho, Tania; Sánchez-Ferrer, Carlos F.; Peiró, Concepción
Abstract : Adipose tissue is acknowledged as an endocrine organ that releases bioactive factors termed adipokines. Visfatin was initially identified as a novel adipokine with insulin-mimetic properties in mice. This adipokine was identical to two previously described molecules, namely, pre-B cell colony-enhancing factor (PBEF) and the enzyme nicotinamide phosphoribosyltransferase (Nampt). Enhanced circulating visfatin/Nampt levels have been reported in metabolic diseases, such as obesity and type 2 diabetes. Moreover, visfatin/Nampt circulating levels correlate with markers of systemic inflammation. In cardiovascular diseases, visfatin/Nampt was initially proposed as a clinical marker of atherosclerosis, endothelial dysfunction, and vascular damage, with a potential prognostic value. Nevertheless, beyond being a surrogate clinical marker, visfatin/Nampt is an active player promoting vascular inflammation, and atherosclerosis. Visfatin/Nampt effects on cytokine and chemokine secretion, macrophage survival, leukocyte recruitment by endothelial cells, vascular smooth muscle inflammation and plaque destabilization make of this adipokine an active factor in the development and progression of atherosclerosis. Further research is required to fully understand the mechanisms mediating the cellular actions of this adipokine and to better characterize the factors regulating visfatin/Nampt expression and release in all these pathologic scenarios. Only then, we will be able to conclude whether visfatin/Nampt is a therapeutical target in cardiometabolic diseases.